2018
DOI: 10.1111/exd.13671
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin K1 and vitamin K2 on the proliferation, cytokine production and regulatory T‐cell frequency in peripheral blood mononuclear cells of paediatric atopic dermatitis patients

Abstract: We estimated the pharmacological efficacy of vitamin K (VK ) and VK on the mitogen-activated peripheral blood mononuclear cells (PBMCs) of paediatric atopic dermatitis (AD) patients. VK suppressed the in vitro proliferation of T-cell mitogen-activated PBMCs of AD patients. In contrast, VK had little effect on the PBMC proliferation. The IL-2 production from the activated PBMCs of AD patients significantly increased (P < .05), while the production significantly decreased by 100 μmol L VK (P < .01). In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Our previous studies highlighted the immunosuppressive effects of vitamins K2 and K3 (Hatanaka et al, 2014;Kusano et al, 2018;Meng et al, 2018;Xu, Meng, Wu, et al, 2019). In the present study, we compared the cytotoxic effects of vitamins K1, K2, and K3 on viabilities of T-cell mitogen-activated PBMCs (Figure 9 and Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies highlighted the immunosuppressive effects of vitamins K2 and K3 (Hatanaka et al, 2014;Kusano et al, 2018;Meng et al, 2018;Xu, Meng, Wu, et al, 2019). In the present study, we compared the cytotoxic effects of vitamins K1, K2, and K3 on viabilities of T-cell mitogen-activated PBMCs (Figure 9 and Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Furthering this finding, K2 decreases proliferation of T-cells from healthy individuals, whereas vitamin K1 had no such effect [103]. This has been further substantiated with T-cells from a larger number of children with pediatric atopic dermatitis and healthy controls, as well as a separate study with patients on dialysis [104,105]. Both these studies demonstrated that K2 decreased the number of activated T-cells, as well as proliferation.…”
Section: Vitamin K2 In Health and Diseasementioning
confidence: 88%
“…[17][18][19] We have previously reported that vitamin Ks have effectively suppress the proliferation of T cell mitogen-activated PBMCs of pediatric atopic dermatitis patients. 14) The present study was carried out to investigate the implications of the regulation of mitogen-activated protein kinase, a signaling-molecule, on the suppressive efficacy of Differences in the amounts of Th1/Th2/Th17 cytokines in the plasma and culture supernatant of PBMCs (CS) between healthy subjects (n = 13) and AD patients (n = 10) were analyzed by Wilcoxon's signed-rank test. In the case of IL-4, a significant difference was observed between the two subject groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that vitamin K2 at 10-100 µM significantly suppressed the T-cell proliferative response and modulated Th1/Th2/Th17 cytokine production in T cell mitogen-activated PBMCs derived from healthy subjects and pediatric atopic dermatitis patients, which are consistent with our previous findings. 13,14) In our previous study, we examined the suppressive effects of vitamin Ks by MTT assays. 14) In the present study in addition to the MTT assay, we confirmed the vitamin K2 efficacy by Calcein AM/PI double staining followed by cell counting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation